Blood supply chain risks in disasters - a fault tree analysis approach. (6th March 2020) - Abtahi, Amir-Reza; Zenouz, Reza Yousefi; Ghaderian, Mohammad-Reza; Aghaie, Afsaneh
Timely delivering of the required blood and blood products to beneficiaries is one of the most critical issues during disaster strikes. Risks are the events that can interrupt the process and hinder the blood supply chains from attaining their predetermined goals. In this paper, we designed a process map that shows the workflow of the blood supply chain visually from donation to the distribution of blood products to the hospital. Then, the risks associated with each activity of the main processes identified. By aggregation of expert judgments using the fuzzy Delphi method, the final list of risks extracted. Then the identified risks were classified and consequently, by using fault tree analysis (FTA), the probability of failure in the blood supply chain in each main level calculated. Findings can help related organisations to manage the risks better and design effective mitigation plans.